Methanol extract of Laportea aestuans reverses uterine hyperplasia in rats - Qudus Ojomo; Esther Agbaje; Joseph Olamijulo (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Laportea aestuans is a medicinal plant used in ethnomedicine as an abortifacient, anthelminthic, anti-fibroid, antipyretic, and anti-microbial agent. Uterine leiomyoma, a menace of reproductive age in women, is characterized by the proliferation of smooth muscle cells (hyperplasia) in the uterus. This study aims to investigate the preventive and curative anti-leiomyoma activity of Laportea aestuans using monosodium glutamate-induced uterine hyperplasia models in female Sprague-Dawley rats. Materials & Methods: The methanol whole plant extract of Laportea aestuans (MELA) was prepared by extracting the pulverized, air-dried whole plant with 2.5 L of methanol in a Soxhlet apparatus, followed by filtration and oven-drying. The acute toxicity of MELA was then assessed using Lorke’s method. Subsequently, three doses of MELA were selected for this study. Uterine hyperplasia was induced with 200 mg/kg p.o. monosodium glutamate (MSG) for 30 days. MELA was either co-administered with the inducing agent (preventive study) or administered post-induction for another 30 days (curative study). The anti-leiomyoma activity of MELA was then assessed through haematological, biochemical, and histopathological findings. Results: Increased serum oestrogen, progesterone, and total cholesterol levels were observed in the untreated fibroid animal groups, but these were significantly attenuated (p < 0.05) in animals treated with different doses of MELA. This correlated with the histopathological findings, as MELA reversed uterine hyperplasia with its therapeutic potential noted from 500 mg/kg. Conclusion: These findings suggest that MELA contains bioactive agents that can reverse MSG-induced uterine hyperplasia. It may therefore be useful in reducing the proliferation of fibroblast cells and managing other symptoms associated with uterine leiomyoma upon successful clinical trials.